Abjection towards Women by Tribes and the State in the Niduparas Erlang’s Burung Kayu - Dewojati, Cahyaningrum; Windayanto, Riqko Nur Ardi (Buletin Al-Turas, 2025)
PurposeThis research aimed to reveal the process of abjection experienced by women by the tribes and the state with its developmentalism ideology in the Burung Kayu by Niduparas Erlang. It also explores the implications of these two regimes, which ultimately contribute to women’s abjection. MethodThis research employed notetaking and literature review techniques for collecting the data. Linguistic data depicting abjection in the novel were interpreted by the researcher according to Julia Kristeva’s theory of abjection. The analysis was supplemented with findings from previous research. Results/findingsThis research presented several findings. Women experienced abjection because the Mentawai tribe practiced a paternalistic culture. This culture reinforced abjection towards women, especially when state intervention with developmentalism ideology was introduced. This development did not provide opportunities for women. Women were abjected as they adhere to their husbands’ will, rather than their own desires. This research sheded light on the fact that although the tribal and state regimes might seem contradictory, they fundamentally reinforce each other in positioning women as abject. ConclusionThis research concluded that abjection was multidimensional, as gender intersected with tribal and state elements supported by developmentalism ideology.